O processo de identificação política de mulheres: estratégias de enfrentamento à exclusão e de fomento à participação segundo trajetórias de envolvimento social - Zschieschang, Thaís (2020)
Based on the political performance of 69 women inserted in local Brazilian public life, this research aims to systematize and broadly validate basic motivating principles, within individual and collective contexts, to encourage the political participation of women from the cultural processes of gender inequality and democratic institutional functioning. The production has as a final product, in addition to systematizing and collecting new data on the described outline, the strategic development of motivating tools for the projection of political life in an aggregating way for women, as an instrument to face the low participatory rate and participatory costs, inherent in its function